2018
DOI: 10.1111/jvh.12884
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic antidepressant use and the risk of fibrosis progression in hepatitis C‐infected persons: Results from ERCHIVES

Abstract: Recent preclinical studies have suggested an antifibrotic role for tricyclic antidepressants (TCA). Using the Electronically Retrieved Cohort of hepatitis C virus (HCV) Infected Veterans, we aimed to evaluate the impact of TCA use on fibrosis progression and development of hepatocellular carcinoma (HCC) among HCV-infected persons. Subjects were categorized according to use of TCAs, selective serotonin reuptake inhibitors (SSRI) or no antidepressants. TCAs or selective serotonin uptake inhibitors use was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Multiple studies have shown that antidepressants may have a protective effect in undifferentiated populations of patients with diverse causes of CLDs. 8,38,39 Nonetheless, such effects were not observed for antidepressants among our specific NAFLD and ALD cohorts in our adjusted analysis with the exception of mirtazapine.…”
Section: Sensitivity Analysismentioning
confidence: 61%
“…Multiple studies have shown that antidepressants may have a protective effect in undifferentiated populations of patients with diverse causes of CLDs. 8,38,39 Nonetheless, such effects were not observed for antidepressants among our specific NAFLD and ALD cohorts in our adjusted analysis with the exception of mirtazapine.…”
Section: Sensitivity Analysismentioning
confidence: 61%
“…We used the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) as the data source for this analysis. ERCHIVES is well defined in numerous previous publications [24][25][26][27][28][29] . Briefly, all persons with HCV infection in the Department of Veterans Affairs healthcare system (VA) diagnosed after October 1, 2001 are identified based on a positive HCV antibody test.…”
Section: Methodsmentioning
confidence: 98%
“…We used the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES), a well‐established and regularly updated national database of HCV infected Veterans and uninfected controls for the current study. ERCHIVES has been described in numerous published studies 2,5,13‐16 . Briefly, all Veterans in care at any of the Veterans Health Affairs (VA) facilities with a positive HCV antibody test from 2001 onwards are included in the database.…”
Section: Methodsmentioning
confidence: 99%